Healthcare Solution Using Machine to Machine Communication - Amodkar, Priyanka; Kulkarni, Smita (Journal of Advance Research in Electrical & Electronics Engineering (ISSN 2208-2395), 2015)
This paper provides a prototype which uses machine to machine communication to provide healthcare solution. ECG and PPG is an important tool to interpret a wide range of heart conditions. Early warning and patient awareness are critical in preventing permanent heart damage and saving much of the heart muscles. These critical conditions motivated us to develop a prototype that provides a long term ECG and PPG monitoring. This prototype consists of ECG and PPG sensors at the patient’s side, that monitors the ECG and PPG and record the signals, this readings are then transmitted with the help of internet to the hospital server. These readings can be accessed in real time by the doctor’s smart phone with the help of android app. Our approach is to provide healthcare solution which can process large amount of biomedical signals through the network that is a combination of internet and sensors. performance over the traditional voltage source inverter fed induction motor drive.